PERSEPSI TENTANG TANAH MENURUT ORANG LAMAHOLOT DI SOLOR BARAT FLORES TIMUR, NUSA TENGGARA TIMUR - Simon Sabon Ola; Yosep B. Kroon (Jurnal Lazuardi, 2020)
This article contains an explanation of the perception of Lamaholot people in West Solor about the land. The land has a vital function in human life. The function of the land is meant can be assumed that there are varied perceptions about land-based on cultural context. The perception intended in this study was expressed through the analysis of the metaphoric meaning contained in various utterances in the Lamaholot language. Based on Culture Linguistic, and referring to the concept of ecology and metaphor, the results of the analysis are as follows: (1) land as a place to live, and (2) a place to make a living. The linguistic expression about the land implied in the research data shows that the people of Lamaholot in West Solor perceive the land as an object containing sacred and magical meaning. The sacredness of the land is expressed in a warning, "don't mess with the land". This expression has implications for attitudes and behavior towards land, including compliance with ownership and boundaries. If the provisions regarding ownership and boundaries are violated, someone will get a serious sanction in the form of death.